Amino Acid Biostimulants Enhance Drought and Heat Stress Tolerance of Creeping Bentgrass (Agrostis Stolonifera L.) - Xunzhong Zhang; Mike Goatley; Maude Focke; Graham Sherman; Berit Smith; Taylor Motsinger; Catherine Roué; Jay Goos (Horticulturae)
Creeping bentgrass (Agrostis stolonifera L.) is an important cool-season turfgrass species widely used for golf course putting greens; however, it experiences a summer stress-induced quality decline in the U.S. transition zone and other regions with similar climates. The objective of this study was to determine the effects of five amino acid biostimulants on creeping bentgrass drought and heat stress tolerance. The five biostimulants, including Superbia, Amino Pro V, Siapton, Benvireo, and Surety, at the rate of 0.22 g of N m−2, were applied biweekly to foliage, and the treatments were arranged in a randomized block design with four replications and were subjected to 56 days of heat and drought stress in growth chamber conditions. The amino acid biostimulants Superbia and Amino Pro V improved the turf quality, photochemical efficiency (PE), normalized difference vegetation index (NDVI), chlorophyll content, antioxidant enzyme superoxide dismutase activity, root growth, and viability and suppressed leaf H2O2 levels when compared to a control. Among the treatments, Superbia and Amino Pro V exhibited greater beneficial effects on turf quality and physiological fitness. The results of this study suggest that foliar application of amino acid biostimulants may improve the summer stress tolerance of cool-season turfgrass species in the U.S. transition zone and other regions with similar climates.